'Ground-Truthing' Chinese Development Finance in Africa: Field Evidence from South Africa and Uganda. Issue 6 (2nd June 2016) - Muchapondwa, Edwin; Nielson, Daniel; Parks, Bradley; Strange, Austin M.; Tierney, Michael J.
ABSTRACT: A new methodology, Tracking Underreported Financial Flows (TUFF), leverages open-source information on development finance by non-transparent, non-Western donors. If such open-source methods prove to be valid and reliable, they can enhance our understanding of the causes and consequences of development finance from non-transparent donors including, but not limited to, China. But open-source methods face charges of inaccuracy. In this study we create and field-test a replicable 'ground-truthing' methodology to verify, update, and improve open-source data with in-person interviews and site visits in Uganda and South Africa. Ground-truthing generally reveals close agreement between open-source data and answers to protocol questions from informants with official roles in the Chinese-funded projects. Our findings suggest that open-source data collection, while limited in knowable ways, can provide a stronger empirical foundation for research on development finance.